Treino de consciência fonológica e intervenção comportamental em ambientes familiar e escolar de crianças com síndrome de Williams - Lima, Solange de Freitas Branco (2015)
The Williams Syndrome (WS) is a disease caused by a deletion in the long arm of chromosome 7 in the region q11.23. Individuals with the syndrome have specific characteristics that interfere in school and social adaptive functioning. Early interventions that require training focused in these areas are recommended for this group. The study’s objective is to evaluate the impact of multimodal program a phonological training and management of behavioral patterns of inattention and hyperactivity/ impulsiveness of a group of children with Williams syndrome. They participated four children with diagnostic confirmation for the syndrome, four mothers and four teachers of their children, totaling 12 participants. The data collection instruments were: a) Phonological Awareness Test by Oral Production (PAT-OP); b) The Child Behavior Checklist for Ages 6-18 and the Teacher’s Report Form for Ages 6-18 (CBCL-6/18 and TRF 6/18); c) Parental Style Inventory (PSI); d) observation Registration behavior problems and appropriate behavior in the classroom; e) Questionnaire for verifying general knowledge of teachers; f) Evaluation of literacy level by the application of words and false Word Reading Competence Test (WRCT) and the Brazil Little Test. The study was developed in four phases: Phase I: Initial evaluation; Phase II: Implementation of the training program for teachers and parents (guide as to behavioral management) and phonological awareness training of children; Phase III: post-intervention evaluation; Phase IV: a segment after six months after the end of the intervention. In the principal results of the assessment of internalizing, externalizing and total problems between phases 1 and 4 of CBCL-6/18, C1 shown a decrease of emotional difficulties and behavioral problems indicators. The results of TRF-6/18 indicated that, although there was also improved, it was not homogeneous. In the total scores of PAT-OP, C1 and C2 obtained a better score in phases 2 and 4. C3 and C4 best score obtained in phases 2, 3, but the phase 4 was better for phase 2. The results obtained by standardizing the WRCT test were different as each child. In conclusion, that the training programs used to make the group of parents and teachers were viable in terms of deployment possibilities. The programs had a positive impact on the acquisition of adaptive behavior and improvement in children’s behavioral difficulties. However, in the familiar and educational context it was verified that in the intervention of these four children was an inconstant use of the orientations and neither all strategies were adopted systematically by the mothers during the study period. Increasing in indicators of phonologic awareness were verified from the performance in rhyme and syllable synthesis tasks. Another data referent to writing and reading competence also indicated that the children who received PA training presented in the study’s last phase skills indicators to decode false words, to varying degrees. The performance of participants C2, C3 and C4 in relation to C1 it was superior in the Brazil Little Test.